THE FREQUENCY OF GESTATIONAL DIABETES MELLITUS AND ASSOCIATED RISK FACTORS AT KHYBER TEACHING HOSPITAL PESHAWAR - Bibi, Saeeda; Saleem, Urooj; Mahsood, Naheed (Journal of Postgraduate Medical Institute, 2015)
Objective: To find out the frequency of gestational diabetes among pregnant women at Khyber Teaching Hospital Peshawar and to explore associated risk factors. Methodology: This cross sectional study was conducted at the department of Gynecology Khyber Teaching Hospital Peshawar from August 2013 to January2014. All pregnant females who fulfill the selection criteria coming for their routine checkup after 24 weeks till 28 weeks were taken in our study by convenient sampling method. Informed consent was obtained from each patientand a questionnaire was administered by researcher herself. Data was analyzedby SPSS version 16. Association of gestational diabetes and risk factorswas studied using chi-square test. Results: A total of 190 pregnant women were included in our study. Frequencyof patients diagnosed as gestational diabetes mellitus on the basis of GTT was 50(26.3%). Risk factors included in the study were significantly associated with development of GDM age of patient (.00), body mass of index (.00), polycysticovarian syndrome (.00), previous history of gestational diabetes mellitus(.00), previous history of macrocosmic baby (.00), and family history of diabetesmellitus (.00). Conclusion: A quarter of the sample population was having GDM and themajor risk factors associated with GDM were age of the patient, body massindex of the patient, polycystic ovarian syndrome, previous history of GDM,previous history of macrosomic baby, family history of diabetes.